PROSES PRODUKSI PART DUDUKAN MOBIL HONDA BR-V STUDI KASUS: PT. PERSADA SELARAS INDONESIA (PSI) - rohendi, muhamad; koswara, engkos (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2023)
In an effort to support the progress of the automotive industry in Indonesia, PT Persada Selaras Indonesia PSI produces quality automotive part products and also carries out the manufacturing process using a stamping machine with a capacity of 110 tons. The purpose of this research is to increase work productivity properly and also produce precision according to production sizes. In this study there were several methods with research stages in which there were observations, literature studies, preparation of book materials, preparation of stamping press machines, setting dies, trial 0, results of measuring data, trial 1 of Maspro and finally the conclusion. The results of the research are the manufacturing process, the Honda Br-V Car Mount Part (Knee Bolster As Out T86 A) by going through the raw material preparation stage with SPCC raw materials, preparing a stamping press machine with a capacity of 110 tons, setting diess on a stamping press machine installing clamping up and down so that the deiss cannot move to anticipate the upper diess and lower diess collide. and the die height setting regulates the machine parameters for deiss with the aim that the part results are in accordance with the standard. The die height parameter has been determined according to the part and machine used, Trial T0 The blanking process, flanging process, Bending process and Pierching process 1-2, Trial T1 After that, it enters mass production. Diess needed in the manufacture of Honda Br-V Car Seat Parts (Knee Bolster As Out T86 A, namely first diess blangking, second diess flanging, third diess bending, fourth pierching 1-2.